Critical Evaluation of Different Techniques for Determining Soil Water Content - Zermeño-González, Alejandro; Munguia-López, Juan; Cadena-Zapata, Martín; Campos-Magaña, Santos Gabriel; Ibarra-Jiménez, Luis; Rodríguez-García, Raúl (IntechOpen, 2012)
None